Diagnostic accuracy of the Cobas 6800 RT-PCR assay for detection of SARS-CoV-2 RNA - Mahmoud, Sally; Ganesan, Subhashini; Raheja, Preety; Cantarutti, Flavia; Ateia, Hagar; Zaher, Walid (Frontiers in Analytical Science, 2022)
Introduction The COVID-19 pandemic has led to the rapid development and launch of several commercial RT-PCR based assays for identification of SARS-CoV-2. However, there is need for peer-reviewed evaluation of these assays to support the clinical performances of such assays. Therefore, in this study we aim to conduct an inhouse evaluation of the automated Cobas 68000 RT-PCR assay in detecting SARS-CoV-2 infections using different pooling techniques. Methods An observational study was conducted to evaluate the clinical performance of the Cobas 6800 SARS-CoV-2 assay in comparison with the Labgun Exofast RT-PCR kit, using both the pooled and the non-pooled sample techniques. A total of 300 nasopharyngeal swab samples, 40 known positive samples and 260 negative samples were used for pooling and the performance was evaluated in three different pool sizes of four, five and six sample pools. Results The sensitivity and specificity of the Cobas 6800 was 100% when compared to the comparator assay. Sample pooling technique showed that specificity was 100% in all pool sizes and the sensitivity varied from 95% in six pooled sample to 100% in both five and four pooled samples. The lower limit of detection was verified to be 25 copies/ml for un-pooled samples and therefore the limit of detection was 100, 125 and 150 copies/ml for four, five and six sample pools respectively. Strong correlation was observed between the Ct values of the target genes of both the assays. Conclusion Cobas 6800 RT-PCR assay is a reliable platform for qualitative and rapid detection of SARS-CoV-2 and can be effectively utilized for pooling of samples with highly efficient performance when the disease prevalence is less.